2015
DOI: 10.1016/j.canlet.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Early or late antibiotic intervention prevents Helicobacter pylori-induced gastric cancer in a mouse model

Abstract: H. pylori infection causes gastritis, peptic ulcers and gastric cancer. Eradicating H. pylori prevents ulcers, but to what extent this prevents cancer remains unknown, especially if given after intestinal metaplasia has developed. H. pylori infected wild-type (WT) mice do not develop cancer, but mice lacking the tumor suppressor p27 do so, thus providing an experimental model of H. pylori-induced cancer. We infected p27-deficient mice with H. pylori strain SS1 at 6-8 weeks of age. Persistently H. pylori-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In addition, H. pylori infection of transgenic mice overexpressing gastrin could induce gastric adenocarcinoma [ 25 ], while gastric carcinogenesis was inhibited when H. pylori eradication therapy was introduced [ 26 ]. H. pylori eradication in mice deficient in p27 similarly reversed premalignant lesions [ 27 ].…”
Section: The Association Of Gastric Cancer With Helicobamentioning
confidence: 99%
“…In addition, H. pylori infection of transgenic mice overexpressing gastrin could induce gastric adenocarcinoma [ 25 ], while gastric carcinogenesis was inhibited when H. pylori eradication therapy was introduced [ 26 ]. H. pylori eradication in mice deficient in p27 similarly reversed premalignant lesions [ 27 ].…”
Section: The Association Of Gastric Cancer With Helicobamentioning
confidence: 99%
“…Real-time qPCR to detect the number of H. pylori in the gastric mucosa A real-time quantitative PCR (qPCR) assay was used to measure the ureC copy number to detect H. pylori given that there is only one copy of the ureC gene exists per bacterium, as previously described (He et al 2002;Shukla et al 2011;Zhang et al 2014). Briefly, 30 mg of gastric tissue for each group was resuspended in 1 ml of PBS and homogenized at full speed for 30 s with a blade-blender homogenizer.…”
Section: Urease Activity Determinationmentioning
confidence: 99%
“…Although antibiotic treatment clearly shows effectiveness in controlling Helicobacter infection in mice, the response in a specific preclinical model is likely to be affected by compounding mutations and genetic polymorphisms carried by the host. H. pylori infection of p27‐deficient mice, for instance, revealed that a combination treatment regime of Omeprazole, Metronidazole, and Clarithromycin controlled infection equally well irrespective of whether the treatment occurred 15 or 45 weeks post‐infection, with both groups scoring similarly for inflammation, epithelial defects, metaplasia, and atrophy . By contrast, H. pylori eradication in INS‐GAS mice was more effective when therapeutic intervention was administered at an early point of infection …”
Section: Helicobacter Infection Modelsmentioning
confidence: 99%